Isolation of a New Antimicrobial/Antitumor Plant Peptide: Biotechnology Prospects for its Use in Cancer and Infectious Diseases Therapies - Guevara, M.G. (2011)
The immune system of multi-cellular organisms comprises a vast arsenal of mechanisms to protect the host from the continuous interactions with infectious microorganisms. Antimicrobial peptides (AMPs) are peptides which protect their hosts against a vast array of microorganisms. These peptides are produced by several species including bacteria, insects, plants, vertebrates and they have been recognized as ancient evolved molecules that have been effectively preserved in mammals. AMPs are expressed on the primary barriers of the organism such as skin and mucosal epithelia, preventing the colonization of host tissues by pathogens. We have previously reported the induction after infection and the cytotoxic activity of potato aspartic proteases (StAPs) towards plant pathogens. Here we show results on the antimicrobial/antitumor activities of these enzymes and of a domain of these enzymes named as StAsp-PSI. StAsp-PSI has structural homology with a family of proteins with antimicrobial/antitumor activity named as SAPLIPs family. Ours results show that StAsp-PSI is able to kill spores of two potato pathogens but not plant cells, in a dose dependent manner. As reported for StAPs (Solanum tuberosum aspartic proteases), StAsp-PSI ability to kill microbial pathogens is dependent on the direct interaction of the protein with the microbial cell wall/or membrane, leading to increased permeability and lysis. Additionally, we demonstrated that, like proteins of SAPLIP family, StAsp-PSI and StAPs are cytotoxic for Gram negative and Gram positive bacteria in a dose dependent manner. The amino acid residues conserved in SP_B (pulmonary surfactant protein B) and StAsp-PSI could explain the cytotoxic activity exerted by StAsp-PSI and StAPs against Gram positive bacteria. On the other hand, results obtained show that StAPs induce apoptosis on Jurkat T cells at short time of incubation in a dose dependent manner. However, not significative effect on the T lymphocytes viability was observed at any time and StAPs concentration assay. StAsp-PSI was able to induce DNA fragmentation, ROS induction and cell cytotoxicity on human breast cancer cells in a dose dependent manner. These results open a new perspective to test these proteins as possible candidates to develop new drugs that would be active against microbes but not against mammalian cells and considerer these proteins as conceptually promising agent in cancer therapy.